(untitled) (Malaysian Journal of Civil Engineering, 2018)
Fatigue cracking is one of the major types of distress in asphalt concrete pavements. Under the action of repeated vehicle loading, the asphalt concrete deteriorates and eventually results in fatigue cracking. This study investigated the effect of temperature, aggregate gradation, nominal maximum aggregate size, and asphalt types on the fatigue life of hot mix asphalt (HMA) mixtures. Six mixtures conforming to JKR/SPJ/2008 were selected, namely asphaltic concrete with a nominal maximum aggregate size of 10 mm (AC10) and 14 mm (AC14), polymermodified asphalt concrete 10 mm (PMA10) and 14 mm (PMA14), and stone mastic asphalt 14 mm (SMA14) and 20 mm (SMA20). Specimens were prepared with the optimum asphalt content using the Marshall Mix design procedure. An indirect tensile test for the resilient modulus was performed according to ASTM D 4123. A fatigue test was also conducted to determine the performance of the mixtures. The specimens were prepared using 80/100 penetration grade asphalt for AC10 and AC14, and PG76 asphalt for PMA10, PMA14, SMA14, and SMA20. Fatigue tests with constant stress were performed using a Universal Testing Machine at 25 ËšC and 40 ËšC at a load of 1000 N. Results show that the fatigue life of asphalt mixtures was lower at 40Ëš C than at 25 ËšC. It was also observed that the mixtures with the smallest nominal maximum aggregate size had a higher fatigue life. The PMAs developed greater fatigue performance than SMAs and ACs due to the aggregate gradation and asphalt type.